2016
DOI: 10.1016/j.scitotenv.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water-sediment regulation of the Xiaolangdi reservoir on the concentrations, characteristics, and fluxes of suspended sediment and organic carbon in the Yellow River

Abstract: Water-sediment regulation (WSR) of the Xiaolangdi Reservoir in the Yellow River is different from other water conservancy projects, with sediment resuspending along the river downstream of the reservoir during water regulation while some suspended sediment depositing during sediment regulation. In this study, samples were collected before, during, and after WSR to investigate the effect of WSR on the suspended sediment and organic carbon downstream of the reservoir. The suspended sediment concentration ([SPS])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…The disturbance effect of the aeration influenced the peak release of the organic matter within 40 min. This is because part of the volatile organic compounds volatilized out of the water during the disturbance process, and a portion of the organic matter was oxidatively degraded [25]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disturbance effect of the aeration influenced the peak release of the organic matter within 40 min. This is because part of the volatile organic compounds volatilized out of the water during the disturbance process, and a portion of the organic matter was oxidatively degraded [25]. …”
Section: Resultsmentioning
confidence: 99%
“…The ammonia nitrogen will be converted to nitrite nitrogen under aerobic conditions and further converted to nitrate nitrogen with sufficient oxygen, while the nitrite nitrogen will degrade to molecular nitrogen in anaerobic or anoxic conditions [25]. Figure 9 shows the change of DO during the intermittent and continuous aeration process.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that the construction of large‐scale water conservancy projects can alter natural hydrological conditions and sediment transport processes downstream (Ruiz‐González et al., ; Xia et al., ). In consequence, upstream and downstream sites of the dam may differ remarkably in their physicochemical properties, which may further influence their bacterioplankton communities.…”
Section: Discussionmentioning
confidence: 99%
“…Because agitation, simulating the river flow and causing the presence of SPS, would pose effects on the diffusion of nitrate from water to bed-sediment, the increased nitrate supply in bed-sediment was also caused by the agitation conditions in addition to the presence of SPS itself which accelerated the production of nitrate. Since SPS concentration also depends on hydrodynamic conditions including river flow velocity in natural rivers (Xia et al, 2016), the results obtained under different agitation rates in this study can reflect the effect of SPS concentration on N-loss from natural rivers.…”
Section: Influence Of Sps Concentration On Denitrification In Bed-sedmentioning
confidence: 92%
“…In addition, according to the above results, the increased proportion of N loss caused by SPS reached 100% when SPS concentration increased to 1 g L -1 in the Yangtze River (TOC ≈ 0.64%). Approximately 46% of the rivers around the world has SPS concentration higher than 1 g L -1 (Xia et al, 2016), and the TOC content in most of these rivers are higher than that in the Yangtze River (Table S4), thus the nitrogen loss in these rivers might increase at least by one time due to the presence of SPS.…”
Section: Importance Of Sps To N Loss From River Systemsmentioning
confidence: 99%